2011
DOI: 10.1007/s10530-011-9989-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of host specificity in explaining the invasion success of the freshwater mussel Anodonta woodiana in Europe

Abstract: Several freshwater mussel species represent some of the most problematic invasive species and have considerably altered ecosystems worldwide. Their invasion potential has been partially attributed to their free-living larvae, which have a high dispersal capability. We investigated the invasion potential of Anodonta (Sinanodonta) woodiana, a species of East Asian unionid mussel established worldwide despite having an obligatory parasitic stage (glochidium), which must encyst on host fish. The invasion success o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(100 citation statements)
references
References 65 publications
(78 reference statements)
2
90
0
8
Order By: Relevance
“…In fact, similar low levels of prevalence and intensity of L. cyprinacea infection in P. parva to those in our study have been reported in the literature (Margaritov and Kiritsis, 2011). The above-mentioned parasite resistance actually refers to the resistance to the possible damaging effects of the parasite, the topmouth gudgeon being otherwise known as a healthy carrier for different parasite species (Spikmans et al, 2013) or being a host for Unonid glochidia, a relation which some authors define more as commensalism (phoresy) than parasitism (Douda et al, 2012). Secondly, we have a host-parasite combination, L. gibbosus and L. cyprinacea, which have lived in sympatry in Europe for more than 100 years, and a newly arrived host species population (P. parva).…”
Section: > Differences In Parasitological Parametersmentioning
confidence: 99%
“…In fact, similar low levels of prevalence and intensity of L. cyprinacea infection in P. parva to those in our study have been reported in the literature (Margaritov and Kiritsis, 2011). The above-mentioned parasite resistance actually refers to the resistance to the possible damaging effects of the parasite, the topmouth gudgeon being otherwise known as a healthy carrier for different parasite species (Spikmans et al, 2013) or being a host for Unonid glochidia, a relation which some authors define more as commensalism (phoresy) than parasitism (Douda et al, 2012). Secondly, we have a host-parasite combination, L. gibbosus and L. cyprinacea, which have lived in sympatry in Europe for more than 100 years, and a newly arrived host species population (P. parva).…”
Section: > Differences In Parasitological Parametersmentioning
confidence: 99%
“…• C. Host specificity is low and European native fish species might serve as potential hosts (Douda et al, 2012). It has been experimentally proven that glochidia might attach to juvenile fish, causing direct mortality (Báskay et al, 1996), resulting in economic loss in fish hatcheries.…”
Section: Mots-clésmentioning
confidence: 99%
“…Carassius species in particular have spread extensively in Turkish waters (Tarkan et al, 2012) and C. gibelio is known to occur in Lake Sapanca (A.S. Tarkan, unpublished data), and is also distributed throughout the country, raising the possibility that A. woodiana may be more widespread in the region than this single case might suggest. A recent study on the invasion success of A. woodiana demonstrated that it is a successful invasive species tolerant of a wide range of environmental conditions (Douda et al, 2012). Monitoring of freshwaters in the vicinity of Lake Sapanca and elsewhere in western Turkey is warranted to measure the potential spread of this species.…”
Section: Discussionmentioning
confidence: 99%